Basal and stimulated calcitonin and procalcitonin by various assays in patients with and without medullary thyroid cancer - Kratzsch, Jürgen; Petzold, Anne; Raue, Friedhelm; Reinhardt, Walter; Bröcker-Preuβ, Martina; Görges, Rainer; Mann, Klaus; Karges, Wolfram; Morgenthaler, Nils; Luster, Markus; Reiners, Christoph; Thiery, Joachim; et al. (Clinical chemistry, 2011)
Calcitonin (CT) is a sensitive marker for evaluation of medullary thyroid cancer (MTC). However, CT measurement can vary with assay- and nonassay-dependent factors, and procalcitonin (PCT) measurement has been proposed for evaluating questionable increases in CT.We tested 2 fully automated CT assays (Immulite [IL] and Liaison [LIA]) and 1 nonautomated CT assay (IRMA, Medipan) and compared these results with PCT (Brahms Kryptor). We evaluated preanalytical conditions and PCT cross-reactivity in sera of 437 patients with clinical conditions associated with hypercalcitoninemia. Additionally, we determined the true “nil” CT concentration in 60 thyroidectomized patients and defined CT cutoff concentrations for pentagastrin stimulation testing in 13 chronic kidney disease (CKD) patients and 10 MTC patients.Markedly decreased CT concentrations were found after storage of sera for >2 h at room temperature and >6 h at 4 °C. Cutoff concentrations for basal and stimulated CT were disease and assay dependent. Proton pump inhibitor therapy was the most frequent reason for increased CT. PCT concentrations were higher in patients with MTC than in patients with CKD without infections (P < 0.001). Whereas IL and LIA demonstrated comparable analytical quality, the IRMA gave increased CT concentrations in nil sera and showed cross-reactivity with PCT in patients with concomitant bacterial infection.IL, LIA, and IRMA detected increased CT concentrations in non-MTC patients and discriminated MTC from CKD patients in pentagastrin tests. PCT assessment may be helpful in the diagnostic work-up of increased CT concentrations in questionable clinical circumstances.
Gesehen am 15.04.2025